Nilai Moral dalam Novel Ra’aytu Ramallah karya Mourid Barghouti (Tinjauan Intrinsik) - Mujadilah nur; Trisnawati S; Haeriyyah (Departemen Sastra Asia Barat, Fakultas Ilmu budaya, Universitas Hasanuddin, 2024)
This research discusses moral values ​​in the novel Ra'aytu Ramallah using intrinsic analysis. This research was conducted because in the novel Ra'aytu Ramallah there are several types of moral values, including individual, religious and social moral values. This research aims to (1) Identify the moral values ​​contained in the Novel Ra'aytu Ramallah by Mourid Barghouti, (2) Analyze the form of conveying moral values ​​in the Novel Ra'aytu Ramallah by Mourid Barghouti using intrinsic review.The type of research used in this research is library research, namely descriptive qualitative. The data collection method is using reading techniques and note-taking techniques. The data analysis technique used is descriptive analysis with stages namely (1) data reduction, (2) data presentation, and (3) drawing conclusions.The results of the research show that (1) There are three types of moral values ​​contained in the novel Ra'aytu Ramallah, namely: the relationship between humans and God (religious morals). There are 3 quotes including gratitude, worshiping God, gratitude, sincerity, and trust in God. There are 13 quotes about human relationships with themselves (Individual morals), including being humble, patient, learning to be independent and not causing trouble to others, being responsible, disciplined, and always being honest. Human relations with other humans in the social sphere (social morals) include helping each other, being polite and friendly towards others, maintaining mutual friendship, giving affection, sharing with others, keeping promises and tolerance between religious communities. (2) The form of conveying moral values ​​in the Novel Ra'aytu Ramallah by Mourid Barghouti is direct and indirect, namely through character descriptions, interpretations and symbols.Keywords: Moral values, Novel, Ra'aytu Ramallah, Intrinsic